HIV Diagnosis and Treatment through Advanced Technologies - Zulfiqar, Hafiza Fizzah; Javed, Aneeqa; Sumbal; Afroze, Bakht; Ali, Qurban; Akbar, Khadija; Nadeem, Tariq; Rana, Muhammad Adeel; Nazar, Zaheer Ahmad; Nasir, Idrees Ahmad; Husnain, Tayyab (Frontiers in Public Health, 2017)
Human immunodeficiency virus (HIV) is the chief contributor to global burden of disease. In 2010, HIV was the fifth leading cause of disability-adjusted life years in people of all ages and leading cause for people aged 30–44 years. It is classified as a member of the family Retroviridae and genus Lentivirus based on the biological, morphological, and genetic properties. It infects different cells of the immune system, such as CD4+ T cells (T-helper cells), dendritic cells, and macrophages. HIV has two subtypes: HIV-1 and HIV-2. Among these strains, HIV-1 is the most virulent and pathogenic. Advanced diagnostic methods are exploring new ways of treatment and contributing in the reduction of HIV cases. The diagnostic techniques like PCR, rapid test, EIA, p24 antigen, and western blot have markedly upgraded the diagnosis of HIV. Antiretroviral therapy and vaccines are promising candidates in providing therapeutic and preventive regimes, respectively. Invention of CRISPR/Cas9 is a breakthrough in the field of HIV disease management.